The Role of Salmonella Enteritidis in Chicken and its Product - Tati Ariyanti; Supar . (Indonesian Center for Animal Research and Development, 2005)
Free pathogenic microorganism of food derived from animals is a prerequisite for human consumption . One of the important pathogenic microorganisms originated from animal product of food is Salmonella. Salmonella enteritidis is frequently found in chicken and spreads vertically as well as horizontally products (eggs, meats and meat products) by direct or indirect contact. Salmonella that contaminated animal product of food can cause foodborne disease in human . Foodborne disease associated with Salmonella occurred in some parts of the world including Indonesia . This problem needs attention from the government, producers and consumers. In the animal production especially chicken, it is demanded to provide animal food and their products free from Salmonella . This is an important indicator of safety food condition . Salmonella control programs in the animal production level begin with raising free-Salmonella day old chick with free Salmonella feed, good farm environmental sanitation . Further more, the monitoring program of Salmonella in farm and post harvest process needs to be conducted . Appropriate handlings of animals and their products are important to obtain food of animal products that are healthy and safe for human consumption . Key word: Salmonella enteritidis, contamination, meat, egg